PAIN MANAGEMENT IN THE CRITICAL ILL PATIENTS WITH MECHANICAL VENTILATOR: A Literature review - -, Chanif (Jurnal Keperawatan Medikal Bedah, 2013)
Pain is the most common experiences and stressors in the critically ill patients, because many sources of pain are present in critical care settings, such as acute illness, surgery, trauma, invasive equipment, nursing and medical interventions. Poor treatment of acute pain may lead to the development of serious complications which may seriously impact the patientâs functioning, quality of life, and well being. The critical nurse must understand the mechanisms, assessment, and appropriate intervention in managing pain. This study aim to describe pain experienced by critical ill patients, identify contributing factors of pain experience, the appropriate pain assessment tools among critically ill patients and critically analyze existing of evidence based interventions tomanage pain among critical ill patients with mechanical ventilator. The authors conducted a comprehensive systematic search of published literature, articles, journals related to pain management in critical ill patients. Pain in the critically ill patients difficult to assess and manage. There are many sources of pain in the critical care setting, and the effect of unrelieved pain have a significant impact on the patientâs recovery. When possible, the patientâs self-report of pain must be obtained. When the patientâs self-report is not available, behavioral indicators represent alternative measure of pain assessment (e.g., BPS, COPT) have been developed for assessment of pain in the critically ill mechanically ventilated population. Both pain management pharmacologic andnonpharmacologic can be used together in relieving pain. Using pharmacologic alone may not fully relieve all aspects of pain. Keyword: Pain management, critical patients, mechanical ventilator